Criminal Justice and Community Psychology: Our Values and Our Work—The Introduction to the Special Issue. Issue 1 (15th March 2021) - Shaw, Jessica; Rade, Candalyn B.; Fisher, Benjamin W.; Freund, Nicole; Tompsett, Carolyn J.
Abstract: This special issue of The American Journal of Community Psychology originated from the Society for Community Research and Action Criminal Justice interest group, with a goal of exploring the work of community psychologists intersecting with criminal justice research, practice, and policy and shaped by our shared values—equity, collaboration, creative maladjustment, social justice, and social science in the service of social justice. In this introduction, we discuss the socio‐historical context of the special issue, followed by an outline of the special issue organization, and brief summary of the included papers. Across 13 papers and an invited commentary, we see the ways in which community psychologists are: (1) delivering and evaluating services, programming, or other supports to address the needs of system‐involved people; and (2) working to improve the systems, structures, and interactions with units of criminal justice systems. Across these two sections, authors highlight the guiding role of our values to influence change within and outside of criminal‐legal systems. Highlights: The values guiding community psychologists uniquely position them to effect change. This includes effecting change within and beyond criminal justice settings. The papers here demonstrate the intersection of community psychology values and criminal justice.